Bell's Palsy as a Potential Predictor Factor for Stroke: A Systematic Literature Review - Gosal, Indra Febryan; Ulfa, Nurul Nisa; Sembiring, Dewanta (Sriwijaya Journal of Neurology, 2024)
Introduction: Bell's palsy, which is caused by herpes simplex virus type 1 (HSV-1) and varicella-zoster virus (VZV), can be a marker for stroke. This study aims to identify and explain the potential of Bell's palsy as a predictor factor for stroke. Methods: The literature search process was carried out on various databases (PubMed, Web of Sciences, EMBASE, Cochrane Libraries, and Google Scholar) regarding Bell’s palsy and stroke. The search was performed using the terms: (1) " Bell’s palsy" AND "morbidity" AND (2) "stroke". This study follows the preferred reporting items for systematic reviews and meta-analysis (PRISMA) recommendations. Results: There are three studies included in this review. A study by Lee et al. stated that there was a significant value in the group of patients aged over 45 years with low socioeconomic status and patients with a history of hypertension, hyperlipidemia, and coronary artery disease (p < 0.005). A study by Kim et al. stated that the Bell's Palsy group had a hazard ratio (HR) (1.19-2.02) for the development of stroke in the future. Meanwhile, a study by Lee et al. showed a significantly higher cumulative incidence of ischemic stroke in Bell's palsy (P < 0.001) compared with controls, which was different from hemorrhagic stroke (P = 0.141). Conclusion: Bell's palsy acts as a simple predictor of stroke.